A biocatalytic approach for the synthesis of known antitubercular and antischistosomal compounds - Zimba, Kabelo Micheal (University of the Witwatersrand, Johannesburg, 2025)
The aim of this project was to develop greener synthetic approaches for producing intermediates of two important therapeutics: the anti-schistosomal drug praziquantel (PZQ) and the anti-tubercular drug isoniazid (INH). These routes were designed to be compatible with biocatalytic methods, particularly lipase- and nitrile hydratase-mediated transformations, which offer more environmentally benign alternatives to traditional chemical processes. For PZQ, five different synthetic strategies were explored to access the key tetrahydroisoquinoline intermediate. The first method employed a Ugi multicomponent reaction using imines, acids, and isocyanides to produce carboxamides: 2-benzoyl-N cyclohexyl-1,2,3,4-tetrahydroisoquinoline-1 carboxamide and 2-benzoyl-N-(tert-butyl)-1,2,3,4-tetrahydroisoquinoline-1 carboxamide. Of these, only 2-benzoyl-N-(tert-butyl)-1,2,3,4-tetrahydroisoquinoline-1 carboxamide underwent successful acid hydrolysis to form the desired tetrahydroisoquinoline-1-carboxylic acid. Attempts to convert this acid to its ester form yielded poor results. The second approach involved partial hydrogenation of isoquinoline - 1-carboxylic acid using heterogeneous catalysis, followed by esterification. While moderate yields of the hydrogenated acid were achieved, esterification remained inefficient. The third approach reversed this sequence, carrying out esterification on the fully aromatic isoquinoline1-carboxylicacid before hydrogenation. The ester formed in good yield, but hydrogenation occurred at the aromatic ring rather than the intended site, giving undesired products. The fourth strategy took a more fundamental approach by building the isoquinoline scaffold from simpler precursors using the Bischler-Napieralski reaction. Although initial steps provided the required precursors in modest yields, only ethyl 2-((3,4- imethoxyphenethyl)amino)-2-oxoacetate cyclised successfully to form the ethyl 6,7-dimethoxy-3,4-dihydroisoquinoline-1-carboxylate, and subsequent reduction attempts were unsuccessful. These outcomes informed a fifth strategy that integrated successful steps from previous approaches. Starting with the partially tetrahydroisoquinoline-1-carboxylic acid, the amine was protected using a Boc group to enable efficient esterification. Subsequent deprotection gave the desired PZQ, methyl 1,2,3,4-tetrahydroisoquinoline-1-carboxylate intermediate in moderate yield, representing a key breakthrough in the synthetic route. With several PZQ intermediates in hand, enzyme-catalysed hydrolysis was investigated. Four ester derivatives were tested using lipases, including Novozyme 435. These were ethyl isoquinoline-1-carboxylate, ethyl 1,2,3,4-tetrahydroisoquinoline-1-carboxylate, 2-tert-butyl 1- methyl 3,4-dihydroisoquinoline- ,2(1H) dicarboxylate and methyl 1,2,3,4-tetrahydroisoquinoline-1-carboxylate. Only one intermediate - ethyl isoquinoline-1- carboxylate - underwent successful hydrolysis to the corresponding acid. Control reactions confirmed that the transformation was enzyme-specific. While the saturated analogues were unreactive under these conditions, this result indicates that, with the right enzyme or optimized conditions, selective enzymatic hydrolysis of PZQ intermediates is feasible. In the case of isoniazid, a nitrile hydratase-catalysed conversion of 4-pyridinecarbonitrile to its corresponding amide intermediate was successfully carried out. The reaction afforded the desired product in good yield, while avoiding over-hydrolysis to the carboxylic acid, a common limitation of conventional methods. This represents a more selective and efficient route to an important INH precursor. Together, these findings demonstrate the potential of integrating biocatalysis with carefully designed chemical synthesis to produce key pharmaceutical intermediates using greener, more sustainable processes. Further research into enzyme selection, reaction conditions, and continuous flow systems may unlock even more efficient and scalable methods for industrial application
A dissertation submitted in fulfilment of the requirements of the Degree of Master of Science, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2025
Keywords: Praziquantel; Isoniazid; Synthesis; Biocatalysis; UCTD; SDG-9: Industry, innovation and infrastructure; SDG-4: Quality education